(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the methods of health-improving students through physical education lessons, restoring and strengthening their physical and mental health. The author analyzes physical exercises, breathing techniques, active games, methods of supporting mental health and ways to form a healthy lifestyle.